Effectiveness of Projection Mapping Technology Development for Education - Adha, Abdillah Hanif Aulia Zulfikar; Juhana, Agus (Jurnal Rekayasa Teknologi Informasi (JURTI), 2025)
One of the main challenges that education will always face in the future is the change in teaching methods. Conventional teaching approaches and strategies are increasingly seen as less able to adapt to the digital society.The development of projection mapping in education opens up opportunities to create interactive learning experiences by transforming classrooms into visual media that support conceptual understanding. The purpose of this study is to find out how education uses projection mapping, the effectiveness of projection mapping in educating and find out what technologies are used. The research method used in this study is a systematic literature review (SLR) with a prism approach (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The Prisma method provides a standard framework that improves quality in the process of systematic review and research replication. This shows that projection mapping is a very effective and innovative tool in creating immersive educational experiences in various contexts, including festivals, museums, and education, where video mapping has been shown to be able to convey messages in an interesting and easy-to-understand way through the combination of narrative, visual, and audio elements. Overall, projection mapping not only expands the boundaries of visual experience, but also offers a more effective and enjoyable educational method, and shows great potential to increase engagement, understanding, and appreciation of art, culture, and education.